Middle meatus microbiome in patients with eosinophilic chronic rhinosinusitis in a Japanese population - Kidoguchi, Masanori; Imoto, Yoshimasa; Noguchi, Emiko; Nakamura, Takako; Morii, Wataru; Adachi, Naoto; Ii, Rieko; Koyama, Keisuke; Aoki, Satoshi; Miyashita, Keisuke; Hosokawa, Yu; Omura, Kazuhiro; et al. (Journal of allergy and clinical immunology, 2023)
Chronic rhinosinusitis (CRS) is a common chronic inflammatory disease and is subdivided into eosinophilic and noneosinophilic forms. There are few reports investigating the nasal microbiome and its pathological functions in patients with CRS. We sought to analyze factors contributing to variations of the nasal microbiome in CRS, and on the basis of these factors, to elucidate whether the bacterial metabolites were related to the pathogenesis. Nasal swabs were collected, and the V3 to V4 variable region of the 16S ribosomal RNA gene was amplified and sequenced. Factors contributing to variations of the nasal microbiome in patients with CRS were compared. The most influential factor was whether CRS was eosinophilic, and we compared α- and β-diversity, bacterial species, and predictive bacterial functions between the 2 patient groups. In addition, the metabolites of the key bacteria were extracted, and we evaluated the predicted bacterial functions in airway epithelial cells. In total, 110 patients with CRS and 33 control subjects were enrolled. On the basis of the factors of variation, it was found that patients with eosinophilic CRS (n = 65) had different microbiomes with weighted UniFrac β-diversity and lower α-diversity compared with those with noneosinophilic CRS (n = 45). A higher abundance of Fusobacterium nucleatum and an increased LPS pathway were observed in patients with noneosinophilic CRS compared with those with eosinophilic CRS. In airway epithelial cells, LPS derived from F nucleatum suppressed the expression levels of ALOX15 induced by TH2 cytokines. The differences in the nasal microbiome may play a key role in the pathophysiology of CRS.